The Varna battlefield – the history of the monument - Kaczmarek, Urszula (Balcanica Posnaniensia. Acta et studia, 1997)
The article presents the history of the commemoration of the battlefield of Varna and the history of the monuments dedicated to Władysław of Varna. The author analyzes the process of shaping the memory of the battle and the ways in which the cult of the king as a hero of Christian Europe was materially preserved. The aim of the study is to show the development of the idea of building monuments on the field of Varna from the nineteenth century to the present day. The author employs an analysis of archival documents, correspondence, monument designs, and historical accounts. The article demonstrates that particular significance was attached to the monument erected in 1856 by the soldiers of Władysław Zamoyski’s division during the Crimean War. The mound with an obelisk was a symbol of the national memory of the Polish émigré community and a testimony to the continuity of patriotic tradition. The author also describes later initiatives, including the construction of a mausoleum in 1935 and the establishment of the Park-Museum of Military Brotherhood in 1964. The results of the analysis indicate that the battlefield of Varna gradually transformed from the site of a historical defeat into a space of symbolic memory and an international cult of the hero.